Auditoría de gestión y su incidencia en la calidad de los servicios de la Cooperativa de Transporte Interprovincial de Pasajeros La Maná Periodo 2021 - Cordonez Alvarez, María Paola (2022)
The current research project resulted in the execution of a management audit, which allowed the researchers to know the Cooperative state in the operational area, whose purpose is to provide improvement measures for transportation and parcel delivery services. In order to develop this research, different types of research were used, such as bibliographic, field, descriptive, and exploratory research; the methods used were: inductive, deductive, and analytical methods, research techniques were also applied, such as observation, surveys, interviews, and questionnaires. Consequently, an audit program was drawn up detailing each phase with its respective activities. At first, the preliminary phase included knowledge of the institution, vision, mission, values, background, organizational structure, legal basis, and so on. The planning process involved objective, reason, audit scope, resources, cut-off date, and marks to be used in the audit. In the execution phase, the authors started directing an interview to the president, a survey to users, a SWOT analysis, and an evaluation of internal control by employing COSO I. In such a manner, the respective calculation of the confidence level and risk per component was made. Through this evaluation, it was possible the detection of findings and recommendations were made to improve certain inconsistencies; therefore, management indicators were applied to show how efficient and effective is currently being the Cooperativa de Transporte La Mana. Despite all its inconsistencies, the authors proceeded to elaborate the incidence matrix for its respective knowledge. This work concluded with the communication of results, internal control, and audit report so that it was exposed in an orderly manner and supported by the corresponding ISAs.